PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III PADA MATA PELAJARAN MATEMATIKA DI SD NEGERI 1 SRIMULYA JAYA - Nurliana, Ika; Khoiriyah, Binti; Pixyoriza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning outcomes for Grade 3 students at SD Negeri 1 Sri Mulya Jaya remain low due to several factors, primarily the fact that teachers have not yet implemented learning models that actively engage students. The learning process remains teacher-centered, with the teacher dominating activities through the delivery of material and practice exercises. Consequently, teachers are required to implement more innovative, student-centered learning approaches. One such approach is the implementation of the "Make a Match" cooperative learning model. This study aims to improve Grade III student learning outcomes in mathematics at SD Negeri 1 Sri Mulya Jaya. The study employs the Classroom Action Research (CAR) method, conducted over two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The research subjects were 20 Grade 3 students at SD Negeri 1 Sri Mulya Jaya. Data collection techniques included observation, interviews, documentation, and learning outcome tests. Data analysis utilized a mixed-methods approach. The research results indicate that implementing the "Make a Match" cooperative learning model can improve Grade 3 students' mathematics learning outcomes at SD Negeri 1 Sri Mulya Jaya. Initial data from daily tests showed a mastery rate of 45% (9 students); this increased to 60% (12 students) in Cycle 1. In Cycle 2, there was a significant increase to 85% (17 students). The increase in mastery from Cycle 1 to Cycle 2 was 25%. Based on these findings, it can be concluded that the implementation of the "Make a Match" cooperative learning model is capable of improving student learning outcomes in mathematics at SD Negeri 1 Sri Mulya Jaya. Keywords: Make a Match learning model, Mathematics, Learning outcomes.